Astragalus polysaccharide (APS) supplement in beagle dogs after castration: Effects on the haematology and serum chemistry profiles, immune response, and oxidative stress status. Issue 1 (30th December 2022) - Luo, Jian‐Bo; Zhang, Lei; Fu, Min; Hong, Yang; Du, Xin‐Yin; Cheng, Guo‐Qiang; Xia, Jie‐Ying; Dong, Han
Abstract: Background: Castration is one of the most common surgical procedures performed in dogs. However, based on increasing evidence, male animals experience significant pain after castration. Astragalus polysaccharide (APS), one of the main bioactive components in A. membranaceus bunge, has been widely used as part of Fu‐Zheng therapy to enhance natural defense mechanisms. Introduction: This study was carried out to determine the effects of supplementing different doses of Astragalus polysaccharide (APS; control, 0 mg/kg; APSL, 400 mg/kg; and APSH, 800 mg/kg) for 8 weeks on the haematology and serum chemistry profiles, immune response, and oxidative stress status in weanling beagle dogs. Methods: After adapting to the experimental environment for 1 week, 18 male beagle dogs (Sichuan Institute of Musk Deer Breeding, China; average initial weight, 3.80 ± 0.43 g; age, 3‐month‐old) were randomly allotted to diets supplemented with three doses of APS (Control, 0 mg/kg; low, 400 mg/kg; and high, 800 mg/kg), referred to as control, APSL, and APSH, respectively; six dogs were assigned to each treatment. The dogs were fed the respective diets twice daily at 08:30 and 16:30 h in sufficient quantity to supply the metabolizable energy requirements for 8 weeks. On day 43 (19 weeks old), the dogs were castrated. On days 42 (prior to castration, 19 weeks old), 50 (day 7 after castration, 20 weeks old), and 57 (day 14 after castration, 21 weeks old) to measure the haematology, blood chemistry, immune response, and oxidative stress status parameters. Results: Based on our findings, the APSH diet decreased weight gain and increased the feed to gain ratio in dogs ( P < 0.05). At 14 days after castration, the wound was almost closed, slightly swollen, dry, and clean in the groups supplemented with APS. In addition, optimal APS supplementation was found to decrease erythrocyte count (RBC), haematocrit (HCT), alkaline phosphatase (ALP), alanine aminotransferase (ALT), C‐reactive protein (CRP), interleukin 1β (IL‐1β), and tumor necrosis factor‐α (TNF‐α) levels, and cortisol and protein carbonyl (PC) concentrations ( P < 0.05). Moreover, the mean corpuscular haemoglobin (MCH) and platelet (PLT) levels, interleukin 10 (IL‐10) and glutathione (GSH) content, and Cu/Zn superoxide dismutase (SOD1), catalase (CAT), and glutathione peroxidase (Se‐GPx) activities were increased in the APS supplemented groups ( P < 0.05) Conclusion: This study demonstrated that supplementing weanling beagle dogs with optimum APS could positively affect wound healing by improving their haematological profile (decreased RBC and HCT content, increased MCH and PLT levels), serum biochemical parameters (decreased ALP and ALT content), immune status (decreased CRP, IL‐1β, and TNF‐α levels; increased IL‐10 content), and antioxidant defense (decreased cortisol and PC content; increased GSH content, and SOD1, CAT, and Se‐GPx activities). However, the detailed mechanism whereby APS regulates these changes requires further investigation. In addition, the results of this study suggest that 400 mg/kg diet is the optimum APS dose for beagle dogs. Abstract : Astragalus polysaccharides improved immune response and antioxidant status in weanling beagle dogs